Conservation and restoration efforts have promoted increases in shorebird populations and the area and quality of their habitat in the Yellow River Delta, China - Houlang Duan; Shaoxia Xia; Xiubo Yu (International Journal of Digital Earth, 2023)
Conservation policies have been formulated for coastal wetlands in China, and exploration of conservation effectiveness based on waterbirds and their habitat is important for guiding conservation actions. We characterized the effects of conservation efforts on shorebird diversity, habitat area and quality using long-term remote sensing data, and shorebird survey data in the Yellow River Delta. From 1997 to 2021, habitat area, quality and population number significantly declined by 49.8% (r = −0.72, p < 0.05), 13.6% (r = −0.72, p < 0.05) and 60.67% (R2 = 0.77, p < 0.05). Before 2012, habitat area (decreased by 38.2%, r = −0.62, p > 0.05, slope = −0.25), quality (decreased by 10.53%, r = −0.68, p > 0.05, slope = −0.008), and population size (significantly decreased by 94.5%, r = −0.95, p < 0.05, slope = −7874.3) declined, and the decline in habitat area significantly contributed to population reductions (r = 0.79, p < 0.05). Since 2012, habitat area (increased by 14.3%, r = 0.71, p > 0.05, slope = 0.12), quality (increased by 17.12%, r = 0.83, p > 0.05, slope = 0.01), and population size (increased by 8.34%, R2 = 0.29, p > 0.05) slightly increased. The coefficients of variation for habitat area and quality, and population size were smaller after 2012 than before 2012. These results suggest that conservation actions maintained the stability of waterbird populations and their habitat; additional actions are needed to mediate the conservation of other degraded habitats along coastal wetlands.